Pesan Moral pada Lagu Diri Karya Tulus: Sebuah Kajian Pustaka Melalui Pendekatan Semiotika Charles Sanders Peirce - Akbarudin; Muhammad N. Abdurrazaq; Supriadi M. (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the moral messages contained in the lyrics of the song "Diri" by Tulus through Charles Sanders Peirce's Semiotics approach. It is motivated by the phenomenon of moral decadence in the digital era, where popular media such as music holds great potential as a communication tool for spreading positive values. The song "Diri" was chosen for its deep, reflective, and humanistic lyrics. The research aims to answer two research questions: (1) What are the moral messages contained in the lyrics of the song "Diri" by Tulus through Charles Sanders Peirce's Semiotics analysis? and (2) How is the interpretation of moral messages related to introspection, self-acceptance, and universal spirituality contained in the song's lyrics? The method used is a literature review with a Charles Sanders Peirce's Semiotics analysis approach. The research data were collected from the lyrics of the song "Diri" and various literature related to morality, psychology, and semiotics. The results show that the lyrics of the song "Diri" contain diverse moral messages, such as increasing self-awareness, forgiveness, self-acceptance, developing qana'ah, and seeking inner peace. These messages are interpreted into three main themes: introspection (as a process of self-reflection), self-acceptance (as the acceptance of one's value and dignity), and universal spirituality (as the search for inner peace).